2008
DOI: 10.1590/s0074-02762008000600010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immunomodulatory and anti-inflammatory effects and phytochemical screening of Alternanthera tenella Colla (Amaranthaceae) aqueous extracts

Abstract: Alternanthera tenella Colla extracts are used in Brazilian traditional folk medicine to treat a variety of infectious diseases as well as inflammation and fever. In this work, the immunomodulatory, anti-inflammatory and potential toxic effects of cold (CAE) and hot (HAE) aqueous extracts of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 26 publications
0
22
0
5
Order By: Relevance
“…This species has antibacterial and antifungal activities and infusions are orally taken for the treatment of infl ammations and infections (BIELLA et al, 2008). This species is considered a weed (SIQUEIRA, 1995), usually eliminated in plantations, and thus becoming as endangered one (DECRETO 42.099, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This species has antibacterial and antifungal activities and infusions are orally taken for the treatment of infl ammations and infections (BIELLA et al, 2008). This species is considered a weed (SIQUEIRA, 1995), usually eliminated in plantations, and thus becoming as endangered one (DECRETO 42.099, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with the water extract of joy weed demonstrated immunomodulatory and antitumor activities on the rats (Moraes et al 1994;Guerra et al 2003) and in vitro antibiotic activity against Gram-positive and Gram-negative bacteria (Silveira and Olea 2009). The major A. tenella components that have been studied are tannins, saponins, flavonoid glycosides and heterosides, such as isorhamnetin, quercetin and kaempferol (Biella et al 2008), as well as other flavonoids, including vitexin and acacetin (Salvador et al 2006). Studies on the chemical composition of species of Alternanthera showed the presence of betalains, betacyanins, betaxanthins, chromo-alkaloids and flavonoids (Brochado et al 2003;Cai et al 2005;Salvador et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Esto apoya el planteamiento de que el extracto estudiado posee un buen potencial antioxidante, lo que debe ser explorado como objetivo de futuras investigaciones. Colla y concluyó que los niveles de taninos y flavonoides podrían tener relación con el potencial antiinflamatorio e inmunomodulador que presentó esta especie (16) .…”
Section: Discussionunclassified